1999
DOI: 10.1128/mcb.19.7.4843
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 Is Phosphorylated at Serine 1497 In Vivo at a Cyclin-Dependent Kinase 2 Phosphorylation Site

Abstract: BRCA1 is a cell cycle-regulated nuclear protein that is phosphorylated mainly on serine and to a lesser extent on threonine residues. Changes in phosphorylation occur in response to cell cycle progression and DNA damage. Specifically, BRCA1 undergoes hyperphosphorylation during late G1 and S phases of the cell cycle. Here we report that BRCA1 is phosphorylated in vivo at serine 1497 (S1497), which is part of a cyclin-dependent kinase (CDK) consensus site. S1497 can be phosphorylated in vitro by CDK2-cyclin A o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 72 publications
1
87
0
Order By: Relevance
“…Our data demonstrates that the principal areas of interaction are the N terminus (aa 1-500) and aa 504-802. Furthermore, BRCA1 is targeted for phosphorylation by numerous cell-cycle kinases including cyclin A/cdk2, cyclin E/cdk2 and cyclin D1/cdk4 (Chen et al, 1996;Ruffner et al, 1999). BRCA1, through its tumor suppressor function, acts to protect cells from unwanted excessive growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data demonstrates that the principal areas of interaction are the N terminus (aa 1-500) and aa 504-802. Furthermore, BRCA1 is targeted for phosphorylation by numerous cell-cycle kinases including cyclin A/cdk2, cyclin E/cdk2 and cyclin D1/cdk4 (Chen et al, 1996;Ruffner et al, 1999). BRCA1, through its tumor suppressor function, acts to protect cells from unwanted excessive growth.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, various cyclin/cdk complexes, including cyclin D, have been shown to phosphorylate BRCA1 (Wang et al, 1997;Ruffner et al, 1999); however, the consequence of cyclin D1/cdk phosphorylation on BRCA1 has not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Immunoprecipitation/ in vitro kinase assays revealed that several cyclins and associated cyclin-dependent kinases (cyclins D and A, CDK2) can associate with and phosphorylate BRCA1 on tyrosine residues in human mammary cell line HBL100 (Wang et al, 1997). In addition, a CDK2/cyclin A or E complex phosphorylates BRCA1 at a CDK consensus phosphorylation site (serine-1497) both in vitro and in vivo (Ruffner et al, 1999).…”
Section: Regulation Of Brca1 Expressionmentioning
confidence: 99%
“…Cyclin E, an essential cyclin that is expressed in late G1 and early S phase, regulates the phosphorylation of many proteins that are important for cell proliferation, including the retinoblastoma protein (RB), 1 BRCA1, 2 and NPAT. 3 Cyclin E is overexpressed in approximately a quarter of all breast tumors 4 and studies have found that cyclin E overexpression and an increase in cyclin E/ CDK2 kinase activity correlates with a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%